Preliminary Evaluation of the Biocontrol Potential of Stethorus punctillum, a Key Natural Enemy of Spider Mites in Northwest China - Haoyu Wang; Dawei Zhang; Huan Guo; Xiaoling He; Bing Liu; Senshan Wang; Yanhui Lu (Agronomy)
Spider mites are globally distributed pests that cause significant damage to a wide range of crops. The use of predators for the control of pest mites is an effective and environmentally sustainable strategy. Stethorus punctillum Weise (Coleoptera: Coccinellidae), a well-known predator of spider mites, has been widely recognized as the primary natural enemy of pest mites in China. However, its pest control efficacy, particularly under field conditions, is not well known. In this study, we evaluated the biocontrol impact of S. punctillum on a key spider mite pest, Tetranychus urticae Koch (Acarina: Tetranychidae), through a combination of laboratory and field experiments. Laboratory assays showed that the predation rates in relation to the prey numbers were consistent with the Holling-II functional response model. The actually maximum predatory numbers of third-instars of S. punctillum, 3-day-old female adults, and male adults on the pest were 116.67, 181.67, and 166.67 mites per day, respectively, corresponding to the theoretically maximum values of 391.26, 498.07, and 413.95 mites per day individually. Field exclusion experiments demonstrated that both larval and adult stages of S. punctillum significantly suppressed spider mite populations’ growth across three different initial prey densities (80, 110, and 140 individuals for larvae; 100, 150, and 200 individuals for adults) on three economically important crops: maize, cotton, and apples. Within 96 h of their introduction, the pest population growth rate was reduced by 13.2–43.2% by larvae and 25.3–51.5% by adults of S. punctillum compared to predator-free control groups. These findings demonstrate that S. punctillum has a significant control efficacy on spider mite populations under both laboratory and field conditions, highlighting its potential as a promising biocontrol agent for integrated spider mite management in Northwest China.